Roles of the Oxidative Stress and ADMA in the Development of Deep Venous Thrombosis - Meral Ekim; M. Ramazan Sekeroglu; Ragıp Balahoroglu; Halil Ozkol; Hasan Ekim (Biochemistry Research International)
Venous thromboembolism has multifactorial origin and occurs in the context of complex interactions between environmental and genetic predisposing factors. Oxidative stress plays an important role in the physiopathology of venous thrombosis. Current study examined the role of oxidative stress and asymmetric dimethylarginine in the development of DVT with the parameters such as serum malondialdehyde (MDA), glutathione peroxidase (GSH-Px), catalase, ADMA, homocysteine, folic acid, vitamin B6, and vitamin B12 levels. Serum MDA levels were found significantly (P<0.005) high in patients with DVT compared with control group. Additionally, serum B6 levels were found significantly (P<0.009) low in patients with DVT compared with healthy volunteers. There were no significant differences between the groups in terms of the other parameters (P>0.05). This study showed that patients with DVT have increased oxidative stress compared with the healthy volunteers whereas there was no significant difference between the groups in terms of serum ADMA levels. Thus serum ADMA levels seemed to be not related with development of DVT.